Theoretical Framework and Methodological Approach for Investigating Potential Associations Between Long COVID and Autism Spectrum Disorder Prevalence - Rudroff, Thorsten (MDPI AG, 2026)
This perspective paper proposes a theoretical framework for investigating potential associations between Long COVID and rising autism spectrum disorder (ASD) prevalence through established epidemiological methodologies. I propose examining temporal correlations, biological mechanisms, and rigorous methodological approaches, including Mendelian randomization, animal models, and evidence-based analyses, that could distinguish association from causation. The proposed framework recognizes autism as neurodiversity while suggesting investigation of environmental factors that may influence expression of genetic predispositions. Hypothesized key mechanisms include neuroinflammation, cytokine alterations, and immune dysfunction. I emphasize the critical distinction between demonstrating statistical associations and establishing causal influence, proposing specific experimental designs that could test causality. This paper presents conceptual frameworks requiring future empirical validation and does not include original data analysis.